The reality of epilepsy in primary care in Rio de Janeiro: the importance of educational projects for better patient care - Lessa, Vanessa Cristina Colares; Martins, Marília Bezerra Magalhães; Vidal, Alexandra Seide Cardoso; Araujo, Leonardo Alves; D'Andrea Meira, Isabella (Arquivos de Neuro-Psiquiatria, 2024)
Background The Basic Health Unit (Unidade Básica de Saúde – UBS, in Portuguese) is the first point of contact in the public healthcare system for people with epilepsy. Primary care professionals need to appropriately diagnose, treat, and refer, if necessary, to tertiary services.Objective To evaluate the knowledge of UBS professionals on the management of patients with epilepsy in Rio de Janeiro.Methods Online questionnaires were performed on the topic of epilepsy before and after exposure to classes taught by epileptologists.Results A total of 66 doctors participated, 54.5% of whom were residents or trained in family medicine. The majority had from 1 to 3 years of practice. Insecurity prevailed in the management of pregnant women and the elderly. Around 59.1% of the participants referred patients with seizures without examinations. A total of 78% of the participants did not correctly classify seizure types, and 2/3 did not define drug-resistant epilepsy. Induction and broad-spectrum drugs were common. The therapeutic decision depended on availability in the basic health unit (UBS) (81.8%), dosage (60.6%), side effects (34.8%), and age (36.4%). Comorbidities and sex influenced 1/4 of the sample. For 23% of the participants, the type of crisis did not affect the choice. Regarding typical non-pharmacological options, 75% of the participants were aware of cannabidiol, 40.9% of surgery, 22.7% of ketogenic diet, and 22.8% of deep brain stimulation/vagus nerve stimulation (DBS/VNS). A total of 90.2% indicated the need for training.Conclusion There are deficits in the knowledge of UBS professionals in the management of epilepsy. Specialized training is imperative to optimize the care offered within SUS.
Keywords: Epilepsy; Primary Health Care; Health Centers; Drug Resistance